Immobilized molybdovanadophosphoric acids on SBA-15 for selective oxidation of alkenes - Raj, N. K. K.; Deshpande, S. S.; Ingle, Rohit H.; Raja, T.; Manikandan, Palanichamy (4th International Symposium on Nanoporous Materials, 2005)
Vanadium substituted molybdophosphoric acids have been immobilized on amine functionalized SBA-15 and characterized by different techniques. Small angle X-ray scattering analysis and SEM technique provide evidence for the structural integrity of the samples. UV-Vis, NMR and IR data confirm the incorporation of molybdovanadophosphoric acids onto the amine functionalized SBA-15. The textural properties of these materials were studied by nitrogen sorption studies. Oxidation of cyclooctene and norbornene was carried out with oxidants in aqueous (aq. H2O2) and non-aqueous (TBHP extracted in dichloroethane) medium. The reactions were carried out with both the neat catalysts (homogeneous) and the immobilized catalysts (heterogenized) and the results were compared. The selectivity of the desired products was always > 99% with the immobilized catalyst with both aq.H2O2 and TBHP. However, while the leaching was negligible in the non-aqueous medium, the aqueous medium leads to considerable leaching. The immobilized catalysts could be separated after the reaction and the reusability of the catalyst has also been demonstrated especially with oxidant in the nonaqueous medium.

Oxidation of norbornene over vanadium-substituted phosphomolybdic acid catalysts and spectroscopic investigations - Raj, N. K. K.; Ramaswamy, A.; Manikandan, Palanichamy (Journal of Molecular Catalysis A-Chemical, 2005)
Oxidation of norbornene has been carried out over mono-, di- and tri-vanadium-substituted phosphomolybdic acid catalysts with aqueous hydrogen peroxide (aq. H2O2) as an oxidant in different solvents. Monovanadium-substituted phosphomolybdic acid catalyst was found to be better than other catalysts for the above reaction and acetonitrile was the suitable solvent. At the optimum temperature of 60 degreesC, the norbornene conversion was 70% and the selectivity for 2,3-epoxy norbornane was 58%. The side products were norborneols and 2-norbornanone. The lower selectivity of 2,3-epoxy norbornane with aq. H2O2 is attributed to the simultaneous formation of other products, norborneols and 2-norbornanone. The norborneols are formed from norbornene by acid-catalyzed reaction. Other oxidants like urea-hydrogen peroxide adduct (UHP) and tert-butyl hydrogen peroxide (TBHP) were also tested for norbornene oxidation reaction. With UHP, the conversion was almost same (69%) as that of aq. H2O2 reaction; however, 2,3-epoxy norbornane was the main product with >97% selectivity. Thus, the overall yield was 66.9% at 60 degreesC after 4 h. The high selectivity with UHP is attributed to the controlled release of H2O2, absence of water and less acidic nature of UHP. With TBHP the selectivity for the epoxide was >96%; however, the conversion was low (27%). A mechanism for the norbornene oxidation is believed to be proceeding via V(5+)-peroxo and V(4+)-superoxo intermediates. NMR, EPR and UV-vis spectroscopic techniques were employed to understand the reaction intermediates and reaction pathways. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: 2; 3-epoxy norbornane; aq. H2O2; epoxidation; EPR; NMR; norbornene; urea-H2O2 adduct; UV-Vis; vanadium-substituted phosphomolybdic acid